Voiced and Voiceless Alveolar Stops of Kermani Accent in stressed and unstressed syllables - Masoumi, Anis; Abolhasanizadeh, Vahideh (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This study aims to compare the voiced and voiceless alveolar stops of Kermani accent in stressed and unstressed syllables. Ten subjects with Kermani accent were asked to repeat 2 words and their plurals for three times. These words are minimal pairs and are different in the first phoneme. Also the effect of these phonemes on the F1, F2 and F0 of the following vowel is measured and compared in stressed and unstressed syllables. Results show that the mean VOT of [t] and [d] in stressed position is more than that in unstressed positions. Unlike F2, F0 and F1 of vowels following [t] and [d] in stressed syllables is more than that in unstressed syllables. Also F0 and F2 of vowels following [+voiced] alveolar stops are more than those following [-voiced] alveolar stops.